Steep Trails - Muir, John, 1838-1914; Badè, William Frederic, 1871-1936 (Salt Lake City, UT : Project Gutenberg, 1995)
"Steep Trails" by John Muir is a collection of essays that captures the author's personal experiences and observations of the natural world, likely written in the late 19th century. This work highlights Muir's deep appreciation for the wilderness, showcasing his adventures across various western landscapes such as California, Utah, Nevada, and the Grand Canyon, while reflecting on the beauty and challenges of nature. The opening of "Steep Trails" introduces Muir's thoughts on the significance of nature and wildness, contrasting it with human culture and cultivation. He recounts his examination of wild sheep and their superior wool, using this observation as a metaphor for the broader idea that nature s creations exist for their own purposes rather than for human use. Muir critiques humanity's tendency to impose cultivation onto nature, arguing that true beauty and utility lie in wildness. Through rich descriptions and philosophical musings, Muir paints a vivid picture of his interactions with the natural landscape, establishing a foundation for the themes of exploration and reverence for the wilderness that permeate the rest of the collection. (This is an automatically generated summary.)
Wild wool -- A geologist's winter walk -- Summer days at Mount Shasta -- A perilous night on Shasta's summit -- Shasta rambles and Modoc memories -- The city of the Saints -- A great storm in Utah -- Bathing in Salt Lake-- Mormon lilies -- The San Gabriel Valley -- The San Gabriel Mountains -- Nevada farms -- Nevada forests -- Nevada's timber belt -- Glacial phenomena in Nevada -- Nevada's dead towns -- Puget Sound -- The forests of Washington --People and towns of Puget Sound -- An ascent of Mount Rainier -- The physical and climatic characteristics of Oregon -- The forests of Oregon and their inhabitants -- The rivers of Oregon -- The Grand Canyon of the Colorado.
Release date is 1995-09-01
Judy Gibson and David Widger
Keywords: West (U.S.) -- Description and travel; Shasta, Mount (Calif. : Mountain); Forests and forestry -- West (U.S.)